STUDI KOMPARASI AKTIVITAS ANTIRADIKAL BEBAS ANTARA EKSTRAK METANOL DAUN DAN KULIT KAYU TUMBUHAN KEDONDONG PAGAR (Lannea coromandelica (Houtt.) Merr) DENGAN METODE PEREDAMAN SENYAWA 1,1-DIPHENYL -2-PICRYLHYDRAZIL (DPPH) - Alwi, Asma; Najib, Ahmad; Waris, Risda (PHARMACY UMI JOURNAL SYSTEM, 2023)
Lannea coromandelica (Houtt.) Merr is one of the plants that hast he potential to have free antiradical activity. The research aimed to compare the free antiradical activity of methanol extract of the bark and leaves of Lannea coromandelica (Houtt.) Merr using the free radical reduction method 1.1 diphenhyl-2-picrylhydrazil (DPPH). The bark nd the leaves extract of the tree were obtained by maceration using methanol. The methanol extract preliminary tests were conducted by TLC using n-hexane: ethyl acetate (9 : 1) and ( 7: 3). The positive results for free antiradical aoctivity marked with purple to yellow spots after DPPH spraying was obtained. The thick bark and leaves extract were then quantitatively tested for free antiradical activity to obtain lC50 values using spectrophotometry at the maximum wavelength of 516 nm. The results of data analysis showed that methanol extract of its bark and leaves had lC50 of 20.778 µg / mL and 19.819 µg / mL, with ascorbic acid as a comparison having an lC50 value of 6.816 µg / mL. So it can be concluded that the methanol extract of the leaves of